Effect of nitrogen level on growth, yield attributes and yield of hybrid varieties of rice (Oryza sativa L.) - Singh, AK; Singh, Divya; Verma, Ravi; Yadav, Atish (ORYZA-An International Journal of Rice, 2023)
A field experiment was conducted during two consecutive seasons of kharif 2020 and 2021 at Agronomy Research Farm, Acharya Narendra Deva University of Agriculture and Technology, Kumarganj Ayodhya (U.P.) to evaluate the effect of nitrogen level on growth, yield attributes and yield of different hybrid varieties of rice (Oryza sativa L.). The experiment was conducted in factorial randomized block design which comprised of 4 levels of nitrogen viz., 0 % RDN, 50 % RDN, 75 % RDN and 100 % RDN and 4 varieties viz., Arize-6444 Gold, Ankur-7576, 27P31 and Shahi-Dawat. Experiment was replicated three times. Results revealed significantly higher growth parameters, yield attributes and yield at 100% of RDN (150 kg N ha-1) which is at par with 75 % RDN (112 kg N ha-1) and significantly superior over 0 % RDN and 50 % RDN (75kg N ha-1) were increased at all stages except days taken to 50% flowering. The growth parameters, yield attributes and yield were increased significantly with Ankur-7576 variety except for length of the panicle (cm) and test weight (g). Ankur-7576 gave a good response in low level of nitrogenous fertilizer and showed good efficiency in utilization of available and applied nitrogen to the crop and is best suitable for obtaining higher yield of hybrid rice.